2013
DOI: 10.1002/oby.20465
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with a SOD mimetic reduces visceral adiposity, adipocyte death, and adipose tissue inflammation in high fat‐fed mice

Abstract: Objective Obesity is associated with enhanced reactive oxygen species (ROS) accumulation in adipose tissue. However, a causal role for ROS in adipose tissue expansion after high fat feeding is not established. The aim of this study is to investigate the effect of the cell permeable superoxide dismutase mimetic and peroxynitrite scavenger Mn(III)tetrakis(4-benzoic acid)porphyrin chloride (MnTBAP) on adipose tissue expansion and remodeling in response to high fat diet (HFD) in mice. Design and Methods Male C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…Moreover, we showed that insulin signalling within WAT was preserved with 1 week of HFD in MCAT mice while lipid-supported mitochondrial ROS emissions, lipid peroxidation and inflammatory signalling were normalised, suggesting excess ROS is the principal mechanism in adipose tissue dysfunction. These findings are in agreement with those of Pires et al who demonstrated that ROS sequestering through the administration of a SOD mimetic reduced WAT inflammation with 5 weeks of HFD [36]. Therefore, mitochondrial ROS emissions are a potential early causal factor in diet-induced insulin resistance in WAT.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we showed that insulin signalling within WAT was preserved with 1 week of HFD in MCAT mice while lipid-supported mitochondrial ROS emissions, lipid peroxidation and inflammatory signalling were normalised, suggesting excess ROS is the principal mechanism in adipose tissue dysfunction. These findings are in agreement with those of Pires et al who demonstrated that ROS sequestering through the administration of a SOD mimetic reduced WAT inflammation with 5 weeks of HFD [36]. Therefore, mitochondrial ROS emissions are a potential early causal factor in diet-induced insulin resistance in WAT.…”
Section: Discussionsupporting
confidence: 92%
“…We also found no effect of MnTBAP on body mass and glucose tolerance in obese and diabetic 9–10 week-old db/db mice after 3–4 weeks of MnTBAP treatment suggesting that the partial restoration of glucose tolerance in ob/ob mice reported by Houstis et al could be due to the much longer duration of MnTBAP treatment in those studies [10]. Although mitochondrial function in skeletal muscle might have been improved by short-term MnTBAP treatment, as we have previously reported in animal models of diet-induced obesity, it is not sufficient to improve systemic glucose homeostasis [34, 35]. Thus, given the higher energetic demand of cardiac mitochondria and potentially greater degrees of oxidative stress, the beneficial impact of MnTBAP on cardiac insulin signaling and glucose transport might be more readily discerned.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown that SOD1 has a critical role in regulating lipid homeostasis [11, 31]. For example, we previously reported that delivering SOD1 as Nano reduced plasma and liver triglycerides [11].…”
Section: Discussionmentioning
confidence: 99%